Designing an Efficient Tree Index on Disaggregated Memory. - Wang, Qing; Lu, Youyou; Shu, Jiwu (Communications of the ACM, 2025)
The article focuses on the design and evaluation of SHERMAN, a high-performance distributed tree index optimized for disaggregated memory using remote direct memory access (RDMA). The authors discuss its design principles, provide an overview of SHERMAN's architecture, and describe key techniques, including the hierarchical on-chip lock and command combination.